Sinking cities [videorecording (DVD)] - Theodore, Lisa (PBS, 2019)
As the earth warms, sea levels rise, and super-storms become more frequent and intense; many major coastal cities will soon be under water. Sinking Cities shows New York, London, Tokyo and Miami preparing for the real-time impact of rising seas and devising colossal new construction projects and groundbreaking solutions aimed at securing their future.